1991
DOI: 10.1007/bf00314963
|View full text |Cite
|
Sign up to set email alerts
|

Prokinetic effect of AS-4370 on gastric emptying in healthy adults

Abstract: The effect of AS-4370 on gastric emptying was investigated in healthy adults using 99mTc-DTPA. Single doses of AS-4370 2.5, 5 or 10 mg or placebo were administered to 12 subjects in a controlled, double-blind, cross-over study. Tests were performed twice weekly in each subject. Thirty min after administration of test drug or placebo, each subject swallowed a bun and orange juice containing 200 microCi nuclide. The radioactivity of the gastric content was measured for 40 min and the activity of the residue was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 4 publications
0
22
0
Order By: Relevance
“…Mosapride is now widely used in Japan as a prokinetic agent after extensive preclinical and clinical evaluation [3,4,5]. It enhanced gastric emptying of the 99m Tc-DTPA liquid meal in healthy volunteers and alleviated gastrointestinal discomfort in patients with non-ulcer dyspepsia, diabetic gastroparesis, or reflex esophagitis.…”
mentioning
confidence: 99%
“…Mosapride is now widely used in Japan as a prokinetic agent after extensive preclinical and clinical evaluation [3,4,5]. It enhanced gastric emptying of the 99m Tc-DTPA liquid meal in healthy volunteers and alleviated gastrointestinal discomfort in patients with non-ulcer dyspepsia, diabetic gastroparesis, or reflex esophagitis.…”
mentioning
confidence: 99%
“…It has been reported that mosapride increases gastric emptying in rats and human (16,17) and enhances motility in the upper GI tract of conscious dogs (12,18). Recent studies have indicated that 5-HT 4 receptors are present in the myenteric plexus and the muscle of the stomach and colon of both humans and guinea pigs (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Although this drug is not new, further studies are of interest to see whether it deserves a more established position for these gastrointestinal indications. (c) Mosapride is a 5-HT4 receptor agonist that accelerates gastric emptying in healthy volunteers and patients with diabetic gastroparesis [84] . In contrast to cisapride, mosapride has little effect on potassium-channel activity and seems to exhibit a significantly lower cardiac dysrhythmogenic potential [85] .…”
Section: Pharmacological Therapymentioning
confidence: 99%